The Effect of Mobile Phone-Based Learning Media with SoundCloud on Listening Skills of Eleventh-Grade Students at MAN 1 Sungai Penuh, Jambi - Nancy Dwinta; Zainul Arifin; Rahmawati Rahmawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The aim of this study is to examine the effect of Mobile Phone-Based Learning using the SoundCloud application on students’ Arabic listening skills among eleventh-grade students at MAN 1 Sungai Penuh, Jambi. This study employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. Data were collected through observation, interviews, and tests. The findings revealed that students in the experimental class achieved higher posttest scores (84.75) compared to the control class (69.42), indicating a substantial improvement in listening performance. The results of the independent samples t-test showed a statistically significant difference between the two groups (t = -10.378, df = 69, p < 0.001), confirming the effectiveness of the treatment. Therefore, it can be concluded that the use of Mobile Phone-Based Learning through the SoundCloud application is more effective than conventional instruction in enhancing students’ Arabic listening skills.